Hanging on to the Edges - Nettle, Daniel (Open Book Publishers, 2021)
What does it mean to be a scientist working today; specifically, a scientist whose subject matter is human life? Scientists often overstate their claim to certainty, sorting the world into categorical distinctions that obstruct rather than clarify its complexities. In this book Daniel Nettle urges the reader to unpick such distinctions—biological versus social sciences, mind versus body, and nature versus nurture—and look instead for the for puzzles and anomalies, the points of connection and overlap. These essays, converted from often humorous, sometimes autobiographical blog posts, form an extended meditation on the possibilities and frustrations of the life scientific. Pragmatically arguing from the intersection between social and biological sciences, Nettle reappraises the virtues of policy initiatives such as Universal Basic Income and income redistribution, highlighting the traps researchers and politicians are liable to encounter. This provocative, intelligent and self-critical volume is a testament to the possibilities of interdisciplinary study—whose virtues Nettle stridently defends—drawing from and having implications for a wide cross-section of academic inquiry. This will appeal to anybody curious about the implications of social and biological sciences for increasingly topical political concerns. It comes particularly recommended to Sciences and Social Sciences students and to scholars seeking to extend the scope of their field in collaboration with other disciplines.